Atomic America - "Tucker, Todd, 1968-" (New York)
"Includes bibliographical references (p. 253-265) and index. The USS United States: the cadre -- Rickover: January 3, 1961, 9:01 pm -- Idaho: the recovery -- The Army: the bachelor party -- The Air Force: Camp Century -- The investigation: the burial -- Enterprise."
Keywords: NUCLEAR REACTOR ACCIDENTS -- IDAHO FALLS (IDAHO);-- HISTORY -- 20TH CENTURY.;NUCLEAR INDUSTRY -- MILITARY ASPECTS -- UNITED;STATES -- HISTORY -- 20TH CENTURY.;IDAHO FALLS (IDAHO) -- HISTORY -- 20TH CENTURY